Bibliometric assessment of the global research output in Jatropha curcas Linn as reflected by papers indexed in Science Citation Index-Expanded. Issue 1 (4th February 2019) - Garg, Kailash Chandra; Kumar, Suresh
Abstract : Purpose: The purpose of this paper is to examine the quantum of research papers and the citations these papers received for the plant Jatropha curcas Linn . Design/methodology/approach: Articles published on Jatropha curcas Linn during 1987–2016 were downloaded from Science Citation Index-Expanded (SCIE) by using the keyword Jatropha* on October 18, 2017. The search resulted in 4, 276 records in all. The authors analyzed only 4, 111 documents which were published as review articles, research articles and proceeding papers using the complete count methodology. The data were analyzed to examine the pattern of growth of output, most prolific countries, institutions and authors. It also identified highly cited authors and journals used for communicating research results. Findings: The study indicates that India, China and Brazil are the main contributors to the field and the pattern of growth indicates a steep rise in publication output especially in the last block of 2015–2016. Most of the prolific institutions and authors were also located in these countries. However, the impact of output was different from the pattern of output. The publication output is scattered in more than 1, 000 journals published from different parts of the globe. Originality/value: The plant of Jatropha curcas Linn is a highly useful plant as a source of biofuel energy. This is the second study in English language on this plant and has used a large set of publication data as compared to the first. The findings of the study may be useful for policy makers as well as for researchers working in the field of biofuel energy.